TITLE WRITTEN WITH CAPITAL LETTERS, CLEAR, SOLID AND INFORMATIVE. JARGON AND ABBREVIATIONS SHOULD BE AVOIDED.WRITING TITLE IN ENGLISH - saipullah saipullah (JURNAL SOCIUS, 2021)
This study aims to describe the implementation of character education in social studies learning which includes planning, implementation, and assessment. This research is a descriptive study with a qualitative approach. The subjects of this study were teachers of social studies at SMP Negeri 1 Tapin Tengah. The object of this research is the implementation of character education in social studies learning at SMP Negeri 1 Tapin Tengah.Data obtained through interviews, classroom observations, and documentation analysis. The data credibility test used in this study is the persistence of observations and the triangulation of methods. The data obtained were then analyzed using the Miles and Huberman analysis model to obtain conclusions.The results obtained in this study are character education has been integrated in social studies learning at SMP Negeri 1 Tapin Tengah, both in planning, implementation, and learning assessment. At the learning planning stage, the social studies teacher at SMP Negeri 1 Tapin Tengah has integrated character values that will be implemented in learning in the syllabus and lesson plans. The implementation of social studies learning at SMP Negeri 1 Tapin Tengah as a whole has integrated character values. Assessment of social studies learning at SMP Negeri 1 Tapin Tengah based on the lesson plans made by the social studies teacher includes affective assessment. Assessment is carried out through observation, questions, and class discussions